On the Name of Book Wrighting: Irma Boom’s “Transformative Crossover” Production - Boom, Irma (2018)
This statement of practice takes the form of a conversation between Danné Ojeda and Irma Boom with a preliminary introduction contextualising Boom’s work. The talk took place in Irma Boom Office, on March 13, 2014 in Amsterdam, and it has been edited for length and readability. Through the introduction and the following conversation, Boom’s practice is positioned within the author-producer-entrepreneur triad and the overlapping margins between these designations. First, design authorship is understood as self-expression that reflects the different ways—whether through technique, material or forms of practice—a designer generates content for communicating her aims. Second, the role of producer is intrinsically related to “the preparation of the work for mechanical reproduction”—in Walter Benjamin’s terms—and the consequent mastering of this technological process in order to generate and communicate meaning through objects and materials. Third, entrepreneurship relates to a business model whereby the designer operates with a high degree of independence, planning as well as resolving managerial responsibilities that make all of the above conditions possible. Examples of Irma Boom’s book design practice will illustrate how she negotiates this author-producer-entrepreneur triad, highlighting how her creative process originates, is prototyped, developed and finally mastered. Closeness to the processes of manufacture proves a vital component of her graphic design practice.